Stimulated luminescence properties of natural alexandrite in response to X-ray irradiation - Silva, A. O.; Amorim, Y. F.; Nunes, M. C.S. [UNESP]; Ulsen, C.; Yoshimura, E. M.; Trindade, N. M. (Elsevier, 2024)
This paper reports for the first time the in-depth study of thermoluminescence (TL) and optically stimulated luminescence (OSL) of Brazilian alexandrite pellets (BeAl2O4: Cr3+) previously exposed to X-rays. Firstly, structural and composition analysis of alexandrite powder was performed to verify the quality of the samples. X-ray diffraction (XRD) pattern revealed that the sample is composed by chrysoberyl (alexandrite) and minor phases as quartz, kaolinite and phlogopite. The presence of several elements, including Cr and Fe, was also detected by X-ray fluorescence (XRF) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Alexandrite pellets exhibited an intense TL signal when previously irradiated with X-ray, showing from the deconvolution five glow peaks centered at 75, 130, 175, 250 and 300 °C. The activation energy (E) and frequency factor (s) were estimated using first-order and general-order kinetic equations. The deconvolution of the OSL curve for alexandrite fit reasonably into three components, characterized as fast, medium and slow. The results obtained showed that the OSL and TL signals of alexandrite pellets vary linearly as a function of the X-ray. The pellets have low fading at room temperature, maintaining 63% of the OSL signal after 10 days of sample storage. Overall, the results suggest that natural alexandrite has TL and OSL sensitivity to X-ray radiation, being a promising material to this radiation.
Keywords: Alexandrite; Dosimetry; Ionizing radiation; OSL; Thermoluminescence